A Body Politic: The Political Writings of Nick Totton. (18th April 2013) - Tudor, Keith
ABSTRACT This article reviews Nick Totton's writing on psychotherapy and politics, and draws on his identification of four aspects of the interface between these two fields, that is, psychotherapy in politics, the psychotherapy of politics, the politics of psychotherapy, and politics in psychotherapy as a way of framing the ground and practice of politically informed psychotherapy or "psy" practice – and, potentially, of psychotherapeutically informed politics. The article then discusses what the author identifies as five central themes regarding the relationship between psychotherapy and politics which are apparent in Nick Totton's writings: the critique of professionalisation, the significance of language, the centrality of power, the inseparability of the political, and the movement beyond dichotomy. Copyright © 2013 John Wiley & Sons, Ltd.